A microfluidic photoreactor enables 2-methylbenzophenone light-driven reactions with superior performance. Issue 50 (3rd April 2018) - Mateos, Javier; Cherubini-Celli, Alessio; Carofiglio, Tommaso; Bonchio, Marcella; Marino, Nadia; Companyó, Xavier; Dell'Amico, Luca
Abstract : A general and scalable microfluidic photoreactor for light-driven reaction of 2-methylbenzophenones was successfully developed. Abstract : Light-driven reactions of 2-methylbenzophenones (2-MBPs) occur with improved yields (up to >98%) and reaction rates (up to 0.240 mmol h −1 ) by using a tailored microfluidic photoreactor (MFP). For the first time, coumarins were converted into 4-benzylated chromanones in high yields (50–93%) and diastereoselectivity (up to >20 : 1 dr), thus by-passing their photo-dimerisation end-reaction.